PENGARUH WAKTU PEMANASAN DAN MEDIA KOROSI TERHADAP LAJU KOROSI BAJA ASTM A36 SEBAGAI BAHAN CHAMBER INCENERATOR - Nugroho, Eko; Surono, Bambang; Aji, Wahyu Seto; Rajabiah, Nurlaila (Universitas Muhammadiyah Metro, 2025)
An incinerator is a machine designed to process solid waste through high-temperature combustion technology. Continuous combustion may lead to corrosion, which is often considered an inevitable problem. The purpose of this study is to investigate how combustion duration and corrosive media affect the corrosion rate. The research method employed was an experimental design involving the heating of material. Tests were conducted to analyze the effect of combustion time and corrosive media in the incinerator chamber on the corrosion rate. The material used was ASTM A36 steel with dimensions of 70 mm × 50 mm × 5 mm. The corrosive media employed were rainwater, H₂SO₄, and HCl. The material was heated at 700 °C for 3, 5, and 7 hours. The immersion time in corrosive media was 30 minutes, followed by a cooling period of 7 days. The results indicated that the highest corrosion rate occurred at a combustion time of 7 hours. Thus, the longer the combustion time, the greater the reaction, resulting in an increased corrosion rate. The use of different corrosive media also influenced the corrosion rate. It was found that the highest corrosion rate was 0.00534 mm/year after 7 hours of heating in HCl solution, while the lowest corrosion rate was approximately 0.00077 mm/year in rainwater after 3 hours of heating. Therefore, prolonged heating not only enhances the reaction but also significantly increases the corrosion rate.